Living Apart Together: The Economic Value of Ethnic Diversity in Cities - Jessie Bakens; Raymond J. G. M. Florax; Henri L. F. de Groot; Peter Mulder (Tinbergen Institute, 2018)
In consumer cities, the presence and location of immigrants impacts house prices through two channels, which both can be valued positively as well as negatively: (i) their presence and contribution to population diversity and (ii) the creation of immigrant-induced consumer amenities like those associated with ethnic restaurants in terms of both quantity as well as diversity. We hypothesize that these two mechanisms create a trade-off in which city dwellers want to live apart yet consume together. We derive a simple intra-city residential location model in which distance to immigrant amenities and the immigrant population in neighborhoods contribute to the explanation of differences in house prices. We use unique micro data of house prices and ethnic restaurants in the city of Amsterdam over the 1996-2011 period to estimate the trade-off between consumers' love for ethnic goods and its variety on the one hand, and ethnic residential composition on the other hand. Our results show the existence of a trade-off in which access to ethnic restaurants compensates for the negative effect of the presence of immigrants on house prices. Diversity of immigrant-induced amenities has an additional positive effect on house prices.
Keywords: D12; D62; J15; R10; 330; amenities; diversity; immigrants; hedonic pricing; propensity score matching